School Readiness of Kindergarten Pupils (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Kindergarten marks the beginning of formal education, making this stage crucial for their overall development. The transition from a play and home environment will now then shift into formal schooling that deters to enable every child to go on a higher milestone of learning. The main purpose of this study is to determine the level of school readiness of the kindergarten based on the perceptions of parents and teachers. The study employed the descriptive-correlational research design to shed light on the empirical data. The parents and teachers of the kindergarten pupils in the Lorma Preschool Department in San Juan, La Union. The data gathered were treated using descriptive and inferential statistics. The findings indicated that parents and teachers perceived a high-level school readiness of the kindergarten learners. The male and female learners significantly varied on their social and emotional development, approaches to learning, and cognitive development. On the other hand, the identified factors do not significantly predict the school readiness of the pupils. Meanwhile, the parents and teachers significantly vary on their perceptions of the school readiness of the pupils, wherein the parent respondents indicated a higher level of readiness of the pupils than their teacher counterparts. Based on this finding, it is recommended that the Kindergarten Instructional Learning Plan should be adopted to enhance the readiness of kindergarten pupils.
Keywords: kindergarten, school readiness, kindergarten instructional learning plan